The NF-κB Pathway: Modulation by Entamoeba histolytica and Other Protozoan Parasites - Chadha, Attinder; Chadee, Kris (Frontiers in Cellular and Infection Microbiology, 2021)
Protozoan parasites have led to worldwide devastation because of their ability to cause infectious diseases. They have evolved as successful pathogens in part because of their remarkable and sophisticated ways to evade innate host defenses. This holds true for both intracellular and extracellular parasites that deploy multiple strategies to circumvent innate host defenses for their survival. The different strategies protozoan parasites use include hijacking the host cellular signaling pathways and transcription factors. In particular, the nuclear factor-κB (NF-κB) pathway seems to be an attractive target for different pathogens owing to their central role in regulating prompt innate immune responses in host defense. NF-κB is a ubiquitous transcription factor that plays an indispensable role not only in regulating immediate immune responses against invading pathogens but is also a critical regulator of cell proliferation and survival. The major immunomodulatory components include parasite surface and secreted proteins/enzymes and stimulation of host cells intracellular pathways and inflammatory caspases that directly or indirectly interfere with the NF-κB pathway to thwart immune responses that are directed for containment and/or elimination of the pathogen. To showcase how protozoan parasites exploits the NF-κB signaling pathway, this review highlights recent advances from Entamoeba histolytica and other protozoan parasites in contact with host cells that induce outside-in and inside-out signaling to modulate NF-κB in disease pathogenesis and survival in the host.